Budaya Organisasi Pesantren Perspektif Organizational Culture dalam Islam - Surip; Muh. Anang Al Aziz (Universitas Muhammadiyah Jakarta, 2026)
This study is motivated by the challenges of modernization, globalization, and the lack of systematic conceptualization that may shift the core values of pesantren organizational culture. The proposed solution is the integration of organizational culture theory with Islamic values to construct a comprehensive conceptual framework. This research aims to formulate the concept of pesantren organizational culture, identify its core values, and explain the mechanisms of their internalization. The study employs a qualitative approach using library research, with the researcher as the primary instrument analyzing classical and contemporary literature through content analysis techniques. The subject of the study consists of relevant academic literature without involving empirical respondents. The findings reveal that pesantren organizational culture represents an integration of spiritual, social, and structural dimensions grounded in the principle of tawhid, manifested through values such as sincerity, trustworthiness, brotherhood, and prophetic leadership of the kiai. These values are internalized through routines, role modeling, and social interactions that shape a collective habitus. In conclusion, the integration of Western theories and Islamic values produces a holistic and contextual understanding, enabling pesantren organizational culture to serve as an adaptive model while preserving its Islamic identity.